From Policy to Practice: Evaluating the Alignment and Disconnect in Outcome-Based Education Curriculum - Mahalli Mahalli; Aliva Rosdiana; Arti Lata (JURNAL AL-TANZIM, 2026)
Outcome-Based Education (OBE) is a curriculum approach that emphasises alignment between graduate learning outcomes, the learning process, and assessment. This study aims to analyse the alignment of curriculum implementation with OBE principles at the design and implementation stages. This study used a qualitative evaluative approach to assess the suitability of the OBE-based curriculum. Data were obtained from 25 RPS (Lecture Plans), a survey of 5 study program heads, academic literature, and national policy documents. Qualitative content analysis was conducted to assess the alignment of CPL (Competency Plans), CPMK (Competency Planning), learning activities, and assessments with OBE principles. The results showed that the curriculum at the design stage was generally aligned with OBE principles. However, inconsistencies were still found during implementation, particularly in learning and assessment, which did not fully reflect student-centred learning and authentic assessment. These findings indicate a gap between curriculum planning and implementation. The contribution of this study is to provide empirical evidence regarding the gap in OBE implementation at the study program level. This implies the need to strengthen lecturer competencies through ongoing training and outcome-based curriculum evaluation.